Intralesional Infiltrations of Cell-Free Filtrates Derived from Human Diabetic Tissues Delay the Healing Process and Recreate Diabetes Histopathological Changes in Healthy Rats - Berlanga-Acosta, Jorge; Fernández-Mayola, Maday; Mendoza-Marí, Yssel; García-Ojalvo, Ariana; Playford, Raymond J.; Guillen-Nieto, Gerardo (Frontiers in Clinical Diabetes and Healthcare, 2021)
Lower limb ulcers in type-2 diabetic patients are a frequent complication that tributes to amputation and reduces survival. We hypothesized that diabetic healing impairment and other histopathologic hallmarks are mediated by a T2DM-induced tissue priming/metabolic memory that can be transferred from humans to healthy recipient animals and consequently reproduce diabetic donor’s phenotypes. We examined the effect of human T2DM tissue homogenates injected into non-diabetic rat excisional wounds. Fresh granulation tissue, popliteal artery, and peroneal nerve of patients with T2DM were obtained following amputation. Post-mammoplasty granulation and post-traumatic amputation-tissue of normal subjects acted as controls. The homogenates were intralesionally injected for 6–7 days into rats’ excisional thickness wounds. Infiltration with the different homogenates caused impaired wound closure, inflammation, nerve degeneration, and arterial thickening (all P < 0.01 vs relevant control) resembling histopathology of diabetic donor tissues. Control materials caused marginal inflammation only. Infiltration with glycated bovine albumin provoked inflammation and wound healing delay but did not induce arterial thickening. The reproduction of human diabetic traits in healthy recipient animals through a tissue homogenate support the notion on the existence of tissue metabolic memory-associated and transmissible factors, involved in the pathogenesis of diabetic complications. These may have futuristic clinical implications for medical interventions.